Professional regulation for Australasian genetic counselors. Issue 2 (5th November 2020) - Hoskins, Cass; Gaff, Clara; McEwen, Alison; Macciocca, Ivan; Pearn, Amy; Shalhoub, Carolyn; Salvemini, Hayley; Berkman, Jennifer; Riley, Kate E.; Williams, Rachel; Milward, Michael; Young, Mary‐Anne
Abstract: As a result of the ongoing global expansion of genetic counseling, the need to formalize a system of professional regulation for genetic counselors was identified in Australasia. In June 2017, under the auspices of the Human Genetics Society of Australasia (HGSA), a working party was convened. The purpose of the working party was to provide strategic leadership for the profession of Australasian genetic counselors with a goal to formalize a national regulatory framework for genetic counselors across both Australian and New Zealand jurisdictions. This was ultimately achieved in Australia through full membership with the National Alliance of Self‐Regulating Health Professions (NASRHP) while the profession of genetic counseling in New Zealand is utilizing this framework to establish their regulation pathway. Regulation has a number of implications for genetic counselors, their employers, and the wider community, with the primary purpose of regulation being protection of the public from harm. This paper details the process of formalizing self‐regulation for genetic counselors in Australasia, by defining professional regulation; outlining the purpose of regulation and the status of regulation for genetic counselors in Australasia and internationally, as well as health professionals more broadly; exploring the challenges of establishing regulation in Australasia; and the next steps for regulation in Australasia. Through detailing this process, the intention is to provide a framework to support genetic counseling colleagues internationally as well as other health professions in Australasia to explore and achieve regulation through their respective jurisdiction.